COMPANY SIZE MODERATES PROFITABILITY, SOLVENCY, COMPANY AGE ON AUDIT DELAY IN THE TECHNOLOGY SECTOR - William Cipta Wijaya; Haninun (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
The purpose of this research is to study how profitability, solvency, and age of a company affect audit delay, and the size of a company moderates profitability, solvency, and age of a company on audit delay. This study has a population in the form of technology companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. By applying the purposive sampling method, researchers managed to obtain 16 companies as samples. Data analysis was carried out using multiple linear regression techniques and moderated regression analysis. The results obtained, partially the age of the company has a negative influence on audit delay, but profitability and solvency have no effect on audit delay. Company size can be proven to be able to moderate the relationship between profitability and audit delay with a positive influence direction. In addition, company size is also able to moderate the relationship between solvency and audit delay with a negative direction of influence. However, company size does not have the ability to moderate the relationship between company age and audit delay. This study contributes to understanding the dynamics of audit delay in the technology sector, by highlighting the importance of effective financial governance management and audit strategies to reduce audit delay.